Visualizing the stages of the educational research methodology into animation infographics for vocational students - Ketut Agustini; Gede Saindra Santyadiputra; Nyoman Sugihartini (Jurnal Pendidikan Vokasi, 2019)
Visualizing something abstract into a concrete object can help students improve their mastery of concepts in learning. The purpose of this study is to visualize the stages of the educational research methodology into an animation infographic media. The method used refers to the instructional development model. The target subjects of this study were students of informatics engineering education study program who had taken courses in educational research methodology. In order to get valid, practical, and effective media, several tests were carried out, such as formative evaluation and effectiveness testing with Hake formula. The results show that the dynamic infographic media produced has gone through expert judgment as follows. (1) Testing by content experts score 1 (very high), testing by the learning design experts scored 0.92 (very high), and testing by learning media experts scored 0.90 (very high). (2) The result obtained from the practicality testing is 86.5%, or it is included in the practical category. (3) The testing of the effectiveness of using the Hake formula obtained N-gain results of 0.8, which belongs to the effective category. It shows that animation infographic media produced is valid, practical, and effective to be used in improving the concept mastery of the stages of educational research methodology in informatics engineering education study program.